Organizational Culture of the Industrial Companies: the Study of the German Construction Concern - Наталья Игоревна Смирнова (Journal of Economic Sociology, 2010)
The research target was to demonstrate the process of appearance and self reproduction of the organizational culture, explained from the social constructivism approach: how the particular system of senses was created due to the interpretations of the organizational symbols of the organizational members. In order to implement this research design the focus was made on the empirical example of the newcomers’ socialization in the company.